'Crystal Macrosetae': Novel Scales and Bristles in Male Arctiine Moths (Lepidoptera: Erebidae: Arctiinae) Filled with Crystallizing Material. Issue 5 (29th October 2019) - Boppré, Michael; Fischer, Ottmar W; Freitag, Hannes; Kiesel, Anita
Abstract: Scales, exoskeletal features characteristic of the Lepidoptera, occur in enormous structural and functional diversity. They cover the wing membranes and other body parts and give butterflies and moths their often stunning appearance. Generally, the patterns made by scales are visual signals for intra- and interspecific communication. In males, scales and/or bristles also make up the androconial organs, which emit volatile signals during courtship. Here, a structurally and putative functionally novel type of scales and bristles is reported: 'crystal macrosetae'. These lack trabeculae and windows, are made up by a very thin and flexible envelope only and contain crystallizing material. In 'crystal scales', there is a flat surface ornamentation of modified ridges, while 'crystal bristles' often show large protrusions. Crystal macrosetae usually cannot be reliably recognized without destruction. Apparently, they serve as containers for large amounts of material that is viscous in living moths, highly hygroscopic, crystallizes when specimens dry up, and can be visualized by scanning electron microscopy. Crystal macrosetae occur in males only, always associated with or making up androconial organs located on various parts of the body, and have numerous forms with diverse surface ornamentation across many species and genera. The newly identified structures and the discovery of crystallizing material in scales and bristles raise many questions and could shed new light on ontogenetic development of macrosetae, and on the biology and physiology as well as the evolution and systematics of Arctiinae. There is evidence that crystal macrosetae occur in other moths too.